A bibliometric study of identity construction in English writing for academic purposes - Yuhan Tian; Donghong Liu (Frontiers in Psychology)
Identity construction is a crucial factor in assessing and enhancing the quality of academic writing. However, identity is elusive and difficult to capture due to its abstract nature. Most existing literature discussed academic writing in a general way, overlooking specific studies on identity construction in articles, theses, and dissertations. This study aims to provide a comprehensive review of studies on identity construction in typical academic writing and assist readers in understanding the development, discoveries, and future trends in this field. It seeks to enlighten scholars and students regarding future research directions and to improve academic writing quality in practice. A bibliometric tool, CiteSpace, was used together with manual close reading. The data were primarily retrieved from the Web of Science database. Keyword co-occurrence and cluster analyses were conducted to describe the current state of research and predict future hotspots. It was found that the literature in this field generally showed an upward trend before 2020. High-frequency keywords primarily relate to literacy, doctoral education, pedagogy, plagiarism, and gender, representing this field’s primary research area. Most clusters exhibit a high level of novelty but have not yet received the attention they deserve because they are situated in the second quadrant of the coordinate diagram as potential clusters. Clusters focusing on socio-cultural identity and the pedagogy of identity construction are more prominent than the other areas. Those focusing on academic (professional) development related to authorial and academic identity are more novel.